TEACHERS' PERCEPTION OF THE IMPLEMENTATION OF THE INDEPENDENT CURRICULUM OF SD NEGERI MASJID LHEU, DARUL IMARAH DISTRICT, ACEH BESAR REGENCY - Yusliana, Yusliana; Yamin, M.; Fitri, Aida (Universitas Syiah Kuala, 2025)
The Independent Learning Curriculum can be a moment for teachers and students to innovate and be independent in improving the quality of learning. Teachers' perceptions of the Curriculum can have a direct impact on student learning. This research aims to determine teachers' perceptions of the implementation of the Merdeka Curriculum at the Mesjid Lheu Elementary School, Darul Imarah District, Aceh Besar Regency. The formulation of the problem in the research is how teachers perceive the implementation of the Independent Curriculum at the Mesjid Lheu Elementary School, Darul Imarah District, Aceh Besar Regency. This research uses a qualitative approach with a descriptive type. The research location was carried out at the Mesjid Lheu Elementary School, Darul Imarah District, Aceh Besar Regency. The subjects in this research were 6 homeroom teachers (classes I to VI). To obtain data, researchers used interview techniques and questionnaires. Analysis techniques through data reduction, data presentation, drawing conclusions and questionnaire analysis. The results of data analysis show that teachers' perceptions of the implementation of the Merdeka Curriculum at SDN Mesjid Lheu are in the sufficient category. Some teachers have difficulty adjusting the curriculum and learning methods because of the diversity of students' characters and time constraints. The average teacher perception score reached 400 (65-76%), with 0% getting a very good rating (88-100). As many as 30% of teachers got good grades (76-88), 20% fair (65-76), and 50% poor (65). So, based on the results of interviews and the results of questionnaires conducted by researchers, it shows that teachers at SDN Mesjid Lheu Teachers' Perceptions of the Implementation of the Independent Curriculum at SD Negeri Mesjid Lheu, Darul Imarah District, Aceh Besar Regency are in the ENOUGH category. Teachers must adapt to adapt the old curriculum to an independent curriculum, teachers must also good at managing time so that there is enough time in the teaching and learning process.